PENERAPAN METODE SNOWBAAL TRHOWING TERHADAP HASIL BELAJAR SISWA PADA MATERI HIDROSFER DI KELAS XI SMA NEGERI 14 TIDORE KEPULAUAN - Ibrahim, Djubaeda; Suaema, Andi; Halek, Dahri Hi (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2024)
The research objective that will be achieved in this research is the application of the snowball thowing learning model to improve student learning outcomes in hydrosphere material in class 10 of SMA Negeri 14 Tidore Islands. This type of research is classroom action research (PTK) using quantitative research methods. The subjects in this research were class XI students at SMA Negeri 14 Tidore Islands with a total of 28 students. The application of the snowball thowing learning model can improve the learning outcomes of class There has been an increase in student learning outcomes which are categorized as